Fly ash-based porous potassium-based carbon dioxide adsorption material and preparation method and application thereof

CN122875191APending Publication Date: 2026-10-09HUANENG CHONGQING LUOWEN POWER CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611250171.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]但原生粉煤灰存在如下缺陷:颗粒致密、孔隙稀少、比表面积偏低,直接作为载体时活性金属钾负载量极低,CO2吸附容量差,无法直接用于烟气CO2捕获

Benefits of technology

1、本发明以粉煤灰替代部分高成本无机载体,搭配高岭土复配制备CO2吸附剂载体,将工业固废粉煤灰转化为CO2捕集吸附材料,原料来源广、成本低、便于规模化制备,实现固废资源化高值利用,降低吸附剂原料成本,同时减轻粉煤灰固废处置压力;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875191A_ABST
    Figure CN122875191A_ABST
Patent Text Reader

Abstract

The present disclosure provides a fly ash-based porous potassium-based carbon dioxide adsorption material and a preparation method and application thereof, and belongs to the technical field of solid waste resource utilization and flue gas carbon dioxide capture. The preparation method comprises the following steps: mixing fly ash, kaolin or metakaolin, a binder and a pore-forming agent to form a mixture; adding deionized water to the mixture and kneading to obtain a plastic slurry; performing extrusion molding, tablet molding, spheroidization molding or honeycomb extrusion molding on the plastic slurry to obtain a wet blank; drying the wet blank to obtain a blank body; calcining the blank body to obtain a fly ash-based porous carrier; and immersing the fly ash-based porous carrier in a potassium carbonate solution, and then drying to obtain the fly ash-based porous potassium-based carbon dioxide adsorption material. The silicon-aluminum skeleton can improve the thermal stability of the carrier and reduce the tendency of the active component to agglomerate and deactivate during multiple adsorption / desorption processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure belongs to the field of solid waste resource utilization and flue gas carbon dioxide capture technology, specifically involving a fly ash-based porous potassium-based carbon dioxide adsorption material, its preparation method, and its application. Background Technology

[0002] Against the backdrop of the comprehensive implementation of the "dual carbon" strategy, the capture of low-concentration CO2 from industrial flue gas is a core technological route for achieving carbon emission reduction and carbon peaking in the industrial sector. Currently, mainstream CO2 solid adsorption materials fall into four main categories: molecular sieves, activated carbon, MOFs, and alkali metal salt-supported inorganic carriers. However, each type of material has significant shortcomings: molecular sieves and MOFs have high raw material and synthesis costs, resulting in poor economic viability under large-scale flue gas conditions; activated carbon has poor thermal stability in high-temperature flue gas and is prone to oxidation and loss; conventional alkali metal-based adsorbents suffer from common problems such as high-temperature migration and aggregation of active components, rapid capacity decay after multiple adsorption-desorption cycles, and insufficient cycle stability, limiting their large-scale industrial application.

[0003] Existing research confirms that aluminum-rich silicon-aluminum systems can significantly increase the melting temperature of materials and effectively inhibit the high-temperature migration, agglomeration, and deactivation of alkaline active components such as K and Ca, making them an ideal system for preparing long-lasting CO2 adsorption carriers. Fly ash solid waste produced by coal-fired power plants is rich in SiO2 and Al2O3, naturally providing a raw material basis for constructing a low-cost silicon-aluminum framework. If fly ash can be developed into a CO2 adsorption carrier, it can significantly reduce the cost of adsorbent raw materials, dispose of massive amounts of fly ash solid waste, solve the environmental problems of land occupation and water and soil infiltration pollution caused by fly ash storage, and achieve synergistic effects of solid waste resource utilization and carbon capture.

[0004] However, raw fly ash has the following defects: dense particles, few pores, and low specific surface area. When used directly as a carrier, the active metal potassium loading is extremely low, and the CO2 adsorption capacity is poor, so it cannot be directly used for CO2 capture in flue gas. Therefore, it is necessary to modify and regulate the porous structure of fly ash and match it with suitable alkaline adsorption active components. Existing fly ash modification and CO2 adsorption related technologies still have multiple problems that are difficult to balance: (1) Some fly ash-based materials need to separate silicon and aluminum components through alkaline leaching, which has a long process flow, high consumption of acid and alkali reagents, and the silicon and aluminum resources in fly ash cannot be integrated and the production cost is high; (2) Most fly ash-derived adsorption carriers can only load organic amine active components. Organic amines in water-containing industrial flue gas are easily hydrolyzed and lost, resulting in a short cycle life; (3) The existing fly ash forming system has insufficient mechanical strength and is easily pulverized during the adsorption and desorption cycle, causing the pressure drop of the reactor bed to rise continuously and affecting the stable operation of the device. Summary of the Invention

[0005] This disclosure aims to at least solve one of the technical problems existing in the prior art, and to provide a fly ash-based porous potassium-based carbon dioxide adsorbent material, its preparation method, and its application.

[0006] One aspect of this disclosure provides a method for preparing a fly ash-based porous potassium-based carbon dioxide adsorbent material, the preparation method comprising: Fly ash, kaolin or metakaolin, binder and pore-forming agent are mixed to form a mixture; Deionized water was added to the mixture and kneaded to obtain a plastic slurry; The plastic slurry is subjected to extrusion molding, sheet molding, spheroidization molding or honeycomb extrusion molding to obtain a wet blank; The wet blank is dried to obtain a green body; The green body was calcined to obtain a fly ash-based porous carrier. The fly ash-based porous carrier is impregnated in potassium carbonate solution and then dried to obtain a fly ash-based porous potassium-based carbon dioxide adsorbent material.

[0007] Optionally, the content ratio of fly ash, kaolin or metakaolin, binder and pore-forming agent is (50-85):(5-25):(3-10):(2-10).

[0008] Optionally, the pore-forming agent is one or more of urea, polyvinylpyrrolidone, starch, and polyethylene glycol; The binder is one or more of silica sol, bentonite, water glass, and attapulgite.

[0009] Optionally, the solid-liquid ratio of the mixture to the deionized water is 1:(0.25-0.40).

[0010] Optionally, the mixing time for adding deionized water to the mixture is 20 to 60 minutes.

[0011] Optionally, the wet blank is dried at a temperature of 80–120°C for 4–12 hours.

[0012] Optionally, the green body is calcined at a temperature of 450–650°C for 1.5–4 hours.

[0013] Optionally, the concentration of the potassium carbonate solution is 5–25 wt%. The fly ash-based porous carrier is impregnated in potassium carbonate solution for 4–12 h, and dried at 100–150 °C for 4–10 h.

[0014] In another aspect of this disclosure, a fly ash-based porous potassium-based carbon dioxide adsorbent material is provided, which is prepared by the preparation method described above.

[0015] In another aspect of this disclosure, an application of a fly ash-based porous potassium-based carbon dioxide adsorbent material is proposed, wherein the fly ash-based porous potassium-based carbon dioxide adsorbent material described above is used for carbon dioxide capture in industrial flue gas.

[0016] This disclosure presents a fly ash-based porous potassium-based carbon dioxide adsorbent material, its preparation method, and its application, which has the following beneficial effects: 1. This invention replaces part of the high-cost inorganic carrier with fly ash and prepares a CO2 adsorbent carrier by combining it with kaolin. It transforms industrial solid waste fly ash into CO2 capture and adsorption material. The raw materials are widely available, low in cost, and easy to prepare on a large scale, realizing the high-value utilization of solid waste resources, reducing the cost of adsorbent raw materials, and alleviating the pressure of fly ash solid waste disposal. 2. After high-temperature calcination, the silica-alumina components in fly ash and kaolin form a stable silica-alumina inorganic framework. The carrier particles have high compressive strength, which can improve the thermal stability of the carrier and reduce the tendency of active components to agglomerate and deactivate during multiple adsorption / desorption processes. 3. By adding a solid pore-forming agent, the pore-forming agent decomposes and releases gas during the calcination process of the carrier, thereby constructing a rich pore structure inside the carrier; 4. The high specific surface area of ​​the silicon-aluminum support provides a large number of dispersion sites for K2CO3, effectively inhibiting the migration, agglomeration and sintering of potassium carbonate active components during multiple cycles of regeneration, avoiding pore blockage and active site coating after active component agglomeration, reducing irreversible deactivation of active components, and ensuring that active components can fully participate in the CO2 adsorption reaction. 5. The CO2 adsorption capacity decreases gradually during the cycle, without rapid decay, and the adsorption-desorption cycle stability is excellent. 6. The material prepared in this disclosure is suitable for capturing low-concentration CO2 in industrial flue gas. Attached Figure Description

[0017] Figure 1 This is a flowchart illustrating the preparation method of fly ash-based porous potassium-based carbon dioxide adsorption material according to a specific embodiment of this disclosure. Figure 2 The combined performance results of Embodiments 1-5 and Comparative Examples 1-2 of this disclosure; Figure 3 This is the cyclic stability data for Embodiment 5 of this disclosure; Figure 4 The effect of the K2CO3 concentration on CO2 adsorption capacity in Example 3 of this disclosure. Detailed Implementation

[0018] To enable those skilled in the art to better understand the technical solutions of this disclosure, the disclosure will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this disclosure and represent a part of the embodiments of this disclosure, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this disclosure without creative effort are within the protection scope of this disclosure.

[0019] As shown in Figure 1, one aspect of this disclosure provides a method S100 for preparing a fly ash-based porous potassium-based carbon dioxide adsorbent material, specifically including the following steps S110~S160: S110. Mix fly ash, kaolin or metakaolin, binder and pore-forming agent to form a mixture.

[0020] In step S110, the content ratio of fly ash, kaolin or metakaolin, binder and pore-forming agent is (50-85): (5-25): (3-10): (2-10).

[0021] In some embodiments, the content of fly ash is preferably 50-85 parts by weight, the content of kaolin or metakaolin is preferably 5-25 parts, the content of binder is preferably 3-10 parts, and the content of pore-forming agent is preferably 2-10 parts.

[0022] In some embodiments, the fly ash is electrostatic precipitator ash or bag filter ash from a coal-fired power plant, with a particle size of 100-300 mesh.

[0023] In some embodiments, the pore-forming agent is one or more of urea, polyvinylpyrrolidone (PVP), starch, and polyethylene glycol (PEG), used for high-temperature decomposition and gas release to create pores, without the need for chemical etching or solvent pore expansion.

[0024] In some embodiments, the binder is one or more of silica sol, bentonite, water glass, and attapulgite.

[0025] In step S110, natural fly ash silica-alumina is combined with kaolin to supplement the aluminum source, forming a high-alumina system, which can significantly improve the thermal stability of the carrier, effectively inhibit the high-temperature migration and sintering agglomeration of potassium salt active components, and solve the defects of pure fly ash carrier being easy to pulverize at high temperatures and losing active components.

[0026] S120. Add deionized water to the mixture and knead to obtain a plastic slurry.

[0027] In step S120, the solid-liquid ratio of the mixture to the deionized water is 1:(0.25-0.40).

[0028] In step S120, the time for kneading the mixture with deionized water is 20 to 60 minutes.

[0029] S130. The plastic slurry is subjected to extrusion molding, sheet molding, spheroidization molding or honeycomb extrusion molding to obtain a wet blank.

[0030] In some embodiments, extrusion molding includes: allowing a plastic slurry to stand and mature for 30 to 120 minutes to eliminate air bubbles inside the slurry and improve its plasticity; continuously feeding the matured plastic slurry into the hopper of an extruder; controlling the screw feed speed to uniformly extrude a strip of wet material; the extruded wet strip is continuous without breakage, without hollows, and has a smooth surface; if cracking occurs, the slurry maturation time is appropriately extended or a small amount of binder is added; the extruded strip material is the wet blank.

[0031] In some embodiments, tableting includes: after the plastic slurry has been allowed to stand and mature, it is divided into lumps, the lumps are laid flat in a mold, and pressure is applied using a hydraulic tablet press. The molding pressure is controlled at 5-15 MPa, and the pressure is held for 30-90 seconds. The mold is opened and a complete sheet-like wet blank is taken out. The sheet-like wet blank is free of delamination and edge defects.

[0032] In some embodiments, spherical forming includes: after the plastic slurry has been left to stand and mature, short cylindrical segments are prepared by an extruder, the short strip-shaped masterbatch is put into a spherical disc and continuously rolled for 5 to 15 minutes. During the rolling process, a small amount of deionized water is intermittently sprayed, and the edges of the materials are gradually rounded by mutual friction. The particle morphology is observed, and the rolling is stopped when the spheres are regular and there are no broken pieces. The material is taken out and sieved to remove fine powder and irregular particles, and complete spherical wet blanks are collected.

[0033] In some embodiments, honeycomb extrusion molding includes: kneading a plastic slurry and sealing it for 2-4 hours to ensure that the slurry is fine and free of hard particles to prevent clogging of the honeycomb mold pores; assembling it into a high-pressure vacuum extruder; turning on a vacuum degassing device (vacuum degree -0.06 to -0.09 MPa) to remove air bubbles from the slurry and prevent holes and cracks from appearing on the honeycomb pore walls; extruding the vacuum-degassed slurry at high pressure and uniform speed from the honeycomb mold to form a continuous honeycomb integral wet body; extruding the honeycomb blank to obtain a wet blank.

[0034] S140. The wet blank is dried to obtain a blank body.

[0035] In step S140, the wet blank is dried at a temperature of 80–120°C for 4–12 hours.

[0036] S150. The blank is calcined to obtain a fly ash-based porous carrier.

[0037] In step S150, the green body is calcined at a temperature of 450–650°C for 1.5–4 h, and the calcination heating rate is 2–10°C / min.

[0038] S160. The fly ash-based porous carrier is impregnated in potassium carbonate solution and then dried to obtain fly ash-based porous potassium-based carbon dioxide adsorption material.

[0039] In step S160, the concentration of the potassium carbonate solution is 5–25 wt%. This K₂CO₃ is the reversible adsorption active component, based on the formula K₂CO₃ + CO₂ + H₂O. The regeneration temperature of the 2KHCO3 reaction is much lower than that of calcium-based adsorbents, which have a regeneration temperature of over 500℃.

[0040] In step S160, the fly ash-based porous carrier is impregnated in potassium carbonate solution for 4–12 h, and the drying temperature is 100–150 °C for 4–10 h.

[0041] In step S160, the impregnation method is atmospheric pressure impregnation, vacuum impregnation, or ultrasonic-assisted impregnation.

[0042] This method uses fly ash as the main raw material, supplemented with kaolin or metakaolin, binder, and pore-forming agent. The mixture is molded, calcined at low temperature to construct a porous carrier, and then impregnated with potassium carbonate solution to obtain a monolithically formed fly ash-based CO2 adsorbent material. The material exhibits a high specific surface area, a high potassium loading, and good cycling stability, demonstrating a high CO2 adsorption capacity under conditions of water-containing flue gas.

[0043] In another aspect of this disclosure, a fly ash-based porous potassium-based carbon dioxide adsorbent material is provided, which is prepared by the preparation method described above.

[0044] In this embodiment, the BET specific surface area of ​​the fly ash-based porous potassium-based carbon dioxide adsorbent is 80–150 m². 2 / g; pore volume is 0.20–0.48 cm³ 3 / g; K element mass fraction is 20-36 wt%; single particle compressive strength is 90-120 N / particle; CO2 adsorption capacity under the conditions of 10 vol% CO2, 10 vol% H2O, and balance N2 is 1.0-2.0 mmol / g.

[0045] In this embodiment, the material retains no less than 88% of its capacity after 20 adsorption / desorption cycles.

[0046] Another aspect of this disclosure proposes an application of a fly ash-based porous potassium-based carbon dioxide adsorbent material, which is used to capture coal-fired flue gas, cement kiln tail gas and industrial low-concentration carbon dioxide gas streams, and is particularly suitable for capturing carbon dioxide in industrial flue gas.

[0047] In this embodiment, the adsorption temperature is 50–70°C, and the desorption regeneration temperature is 160–190°C.

[0048] The preparation method and specific applications of fly ash-based porous potassium-based carbon dioxide adsorbent materials will be further illustrated below with reference to specific embodiments: Example 1 This example illustrates a method for preparing fly ash-based porous potassium-based carbon dioxide adsorbent materials: S1. Mix 70 g of fly ash, 15 g of kaolin, 5 g of bentonite, and 5 g of PVP to form a mixture. S2. Add deionized water to the mixture to adjust the solid-liquid ratio to 1:0.32, and then knead for 30 minutes to obtain a plastic slurry. S3. The plastic slurry is extruded to obtain cylindrical particles with a diameter of 3 mm; S4. Dry the wet billet at 110℃ for 8 hours to obtain the green body; S5. The green body is calcined at 550℃ for 2 h to obtain a fly ash-based porous carrier. S6. The fly ash-based porous carrier was impregnated in a 20 wt% potassium carbonate solution for 8 hours and then dried at 120℃ for 6 hours to obtain a fly ash-based porous potassium-based carbon dioxide adsorbent material (A1).

[0049] Furthermore, the prepared material was subjected to CO2 adsorption. The desorption cycle performance test procedure and test conditions are as follows: Test temperature: 60℃ Desorption temperature: 180 ℃ Flue gas composition: 10 vol% CO2 + 10 vol% H2O, balance N2 Airspeed: 3000 h -1 The fly ash-based porous potassium-based CO2 adsorbent prepared in this embodiment was effective at an adsorption temperature of 60℃, a desorption temperature of 130℃, a flue gas composition of 10 vol% CO2 + 10 vol% H2O, with N2 as the equilibrium gas, and a space velocity of 3000 h⁻¹. -1 Fixed-bed circulation tests were conducted under these conditions. As shown in Table 1 and Figure 2 As shown, the specific surface area of ​​BET is 128.9 m².2 The sample has a potassium loading of 35.6 wt%, a compressive strength of 103 N, and a CO2 adsorption capacity of 1.86 mmol / g. It undergoes 20 adsorption cycles. After desorption cycling, the capacity retention was 91.9%. This indicates that the material in this embodiment possesses high adsorption capacity, excellent mechanical strength, and good cycling stability.

[0050] Example 2 Replace 5 g of PVP in Example 1 with 5 g of urea, and follow the same steps as in Example 1 to obtain fly ash-based porous potassium-based carbon dioxide adsorbent material (A2).

[0051] As shown in Table 1 and Figure 2 As shown, the specific surface area of ​​BET is 118.7 m². 2 The sample has a potassium loading of 31.8 wt%, a compressive strength of 95 N, a CO2 adsorption capacity of 1.53 mmol / g, and a capacity retention of 90.6% after 20 adsorption-desorption cycles.

[0052] Example 3 The PVP 5 g in Example 1 was replaced with PVP 2 g, the K2CO3 impregnation concentration was 10 wt%, and the remaining steps were the same as in Example 1, to obtain fly ash-based porous potassium-based carbon dioxide adsorbent material (A3).

[0053] As shown in Table 1 and Figure 2 As shown, the specific surface area of ​​BET is 99.6 m². 2 The sample has a potassium loading of 21.1 wt%, a compressive strength of 110 N, a CO2 adsorption capacity of 1.05 mmol / g, and a capacity retention of 87.3% after 20 adsorption-desorption cycles.

[0054] Furthermore, such as Figure 4 As shown in the figure, this embodiment also tested K2CO3 impregnation concentrations of 5 wt%, 15 wt%, and 25 wt%, and the results are as follows. Figure 4 As shown, the potassium load of the sample continued to increase with the increase of the impregnation solution concentration; the CO2 adsorption capacity first increased rapidly, and the capacity increase tended to be gradual after the concentration exceeded 20 wt%.

[0055] Example 4 The PVP 5 g in Example 1 was replaced with PVP 10 g, the calcination temperature was increased to 600℃, and the remaining steps were the same as in Example 1, to obtain fly ash-based porous potassium-based carbon dioxide adsorbent material (A4).

[0056] As shown in Table 1 and Figure 2 As shown, the specific surface area of ​​BET is 121.4 m².2 The sample has a potassium loading of 29.2 wt%, a compressive strength of 96 N, a CO2 adsorption capacity of 1.47 mmol / g, and a capacity retention of 90.1% after 20 adsorption-desorption cycles.

[0057] Example 5 The extrusion molding method in Example 1 was replaced with honeycomb extrusion molding, with a honeycomb pore density of 200 cpsi. The remaining steps were the same as in Example 1, and a fly ash-based porous potassium-based carbon dioxide adsorbent material (A5) was obtained.

[0058] The test procedure was the same as in Example 1, with the regeneration temperature set to 170°C. The results are shown in Table 1 and... Figure 2 As shown, the specific surface area of ​​BET is 132.5 m². 2 The sample has a potassium loading of 34.9 wt%, a compressive strength of 108 N, a CO2 adsorption capacity of 1.91 mmol / g, and a capacity retention of 92.3% after 20 adsorption-desorption cycles.

[0059] Furthermore, this embodiment also tested the cyclic stability, as shown in Table 2 and... Figure 3 As shown, the CO2 capacity was 1.91 mmol / g after 1 cycle, 1.87 mmol / g after 5 cycles, 1.82 mmol / g after 10 cycles, 1.79 mmol / g after 15 cycles, and 1.76 mmol / g after 20 cycles. This indicates that the aluminum-rich fly ash-kaolin composite framework significantly inhibits potassium salt sintering migration, the capacity decay during the cycling process is gradual without rapid drop, and the long-cycle cycling performance is excellent.

[0060] Table 1. Cyclic adsorption performance test results of Examples 1-5

[0061] Table 2 Cyclic stability data for Example 5

[0062] Comparative Example 1 This example involved direct impregnation with potassium carbonate solution without any pore-forming treatment. All other steps were the same as in Example 1, yielding sample (C1). The test results are shown in Table 4 and... Figure 2 As shown, the specific surface area of ​​BET is 46.2 m². 2 / g, CO2 adsorption capacity is 0.72 mmol / g.

[0063] Table 4 Results of Cyclic Adsorption Performance Tests for Comparative Example 1

[0064] Comparative Example 2 This example did not involve impregnation with potassium carbonate solution; the remaining steps were the same as in Example 1, yielding sample (C2). The test results are shown in Table 5 and... Figure 2 As shown, the specific surface area of ​​BET is 101.4 m². 2 / g, CO2 adsorption capacity is 0.17 mmol / g.

[0065] Table 5. Results of Cyclic Adsorption Performance Tests for Comparative Example 2

[0066] In summary, Comparative Example 1, lacking a pore-forming process, has no porous structure and thus a low CO2 adsorption capacity. Comparative Example 2, without impregnation with potassium carbonate solution, only exhibits physical adsorption through pores, resulting in a low BET specific surface area and low CO2 adsorption capacity. Compared to Comparative Examples 1-2, Examples 1-5 of this invention, through a combination of fly ash and kaolin with a solid pore-forming agent and impregnation with potassium carbonate solution, significantly improve the BET specific surface area and enhance the pore structure of the carrier. The higher specific surface area provides sufficient loading sites for the potassium active component, leading to a significant increase in CO2 adsorption capacity. Therefore, the above examples utilize fly ash to construct a low-cost porous silica-alumina framework and, by controlling the pore structure and loading the K2CO3 active component through a pore-forming agent, achieve highly efficient CO2 adsorption. The resulting material possesses a high specific surface area, good mechanical strength, high CO2 adsorption capacity, and excellent cycle stability, making it suitable for industrial flue gas carbon capture.

[0067] It is understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of this disclosure, and this disclosure is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and substance of this disclosure, and these modifications and improvements are also considered to be within the scope of protection of this disclosure.

Claims

1. A method for preparing a fly ash-based porous potassium-based carbon dioxide adsorbent material, characterized in that, The preparation method includes: Fly ash, kaolin or metakaolin, binder and pore-forming agent are mixed to form a mixture; Deionized water was added to the mixture and kneaded to obtain a plastic slurry; The plastic slurry is subjected to extrusion molding, sheet molding, spheroidization molding or honeycomb extrusion molding to obtain a wet blank; The wet blank is dried to obtain a green body; The green body was calcined to obtain a fly ash-based porous carrier. The fly ash-based porous carrier is impregnated in potassium carbonate solution and then dried to obtain a fly ash-based porous potassium-based carbon dioxide adsorbent material.

2. The preparation method according to claim 1, characterized in that, The content ratio of fly ash, kaolin or metakaolin, binder and pore-forming agent is (50-85):(5-25):(3-10):(2-10).

3. The preparation method according to claim 1, characterized in that, The pore-forming agent is one or more of urea, polyvinylpyrrolidone, starch, and polyethylene glycol; The binder is one or more of silica sol, bentonite, water glass, and attapulgite.

4. The preparation method according to claim 1, characterized in that, The solid-liquid ratio of the mixture to the deionized water is 1:(0.25-0.40).

5. The preparation method according to claim 1, characterized in that, The mixing time for adding deionized water to the mixture is 20 to 60 minutes.

6. The preparation method according to claim 1, characterized in that, The wet blank is dried at a temperature of 80–120°C for 4–12 hours.

7. The preparation method according to claim 1, characterized in that, The green body is calcined at a temperature of 450–650°C for 1.5–4 hours.

8. The preparation method according to claim 1, characterized in that, The concentration of the potassium carbonate solution is 5–25 wt%. The fly ash-based porous carrier is impregnated in potassium carbonate solution for 4–12 h, and dried at 100–150 °C for 4–10 h.

9. A fly ash-based porous potassium-based carbon dioxide adsorbent material, characterized in that, The fly ash-based porous potassium-based carbon dioxide adsorbent material is prepared by the preparation method described in any one of claims 1-8.

10. An application of a fly ash-based porous potassium-based carbon dioxide adsorbent material, characterized in that, The fly ash-based porous potassium-based carbon dioxide adsorbent material described in claim 9 is used for carbon dioxide capture in industrial flue gas.